A new consistent and high-precision earthquake catalogue for the Taupō Volcanic Zone, New Zealand - Finnigan Illsley-Kemp; Eleanor Mestel (Seismica)
The Taupō Volcanic Zone is a ~300 km long, volcanically active region in the North Island of Aotearoa New Zealand. As well as hosting numerous active volcanoes, it is also one of the most seismically active parts of the country. In this study, we present a new consistent and high-precision earthquake catalogue for the Taupō Volcanic Zone from 2007 to 2023. This catalogue was produced through the detection of earthquake phase arrivals, association of these arrivals, and finally earthquake location and relocation using a three-dimensional velocity model. The final catalogue contains 86,579 individual earthquakes, 65% of which also have a high-precision relative relocation hypocentre. The catalogue contains a huge amount of information on multiple volcanic, geothermal, and tectonic events. We make the catalogue freely available in the hope that it will be used for future research and development in the Taupō Volcanic Zone.